Równowaga pomiędzy nastawieniem na posiadanie a poczuciem odpowiedzialności w życiu - Czerw, Monika; Karpuszenko, Elena; Kukla, Daniel (Kultura-Społeczeństwo-Edukacja, 2023)
The present times are, in a way, focused on success and striving to occupy the highest social position. The attitude and the sense of responsibility are shaped throughout life in the process of social development, which thus contributes to the achievement of specific attributes conditioning the functioning in a given community. In the study in the light of the conducted source analyzes and own research, the issue of maintaining the balance between living life and having an attitude towards having is presented, which is also related to the sense of own responsibility.